In vitro propagation of Citrullus lanatus Thumb. from nodal explants culture - Khatun, MM; Hossain, MS; Haque, MA; Khalekuzzaman, M (Journal of the Bangladesh Agricultural University, 2011)
A standard protocol was established for rapid in vitro propagation of watermelon (Citrullus lanatus Thumb.) from nodal explants of field grown plant. Multiple shoot proliferation was achieved from nodal explants on MS medium supplemented with 1.0 mg/l BAP + 0.2 mg/l NAA within 30 days of inoculation. The elongation of shoots was obtained on the same medium. Highest percentage of root induction was achieved on MS medium supplement with 1.0 mg/l IBA within 25 days of culture. Well rooted plantlets were transferred to small pots and after proper acclimatization the plantlets were transplanted in the field condition, where 80% plantlets were survived and grew successfully. Keywords: In vitro regeneration; Nodal explant; Citrullus lanatus DOI: 10.3329/jbau.v8i2.7926 J. Bangladesh Agril. Univ. 8(2): 203-206, 2010